Clinical Study of Restless Leg Syndrome Accompanied by Psychological Symptoms Induced by High-Dose Treatment With Madopar - Zhu, Lei; Li, Jing; Ren, Chongyang; Zhang, Mei; Xue, Min; Yu, Chuanqing; Zhang, Weili (Frontiers in Psychiatry, 2019)
Objectives: Some neurological disorders demonstrate indistinguishable psychological symptoms at an early stage, especially when accompanied by jitters similar to those in Parkinson’s disease. During dopamine replacement therapy, some patients display restless leg syndrome (RLS)-like symptoms. Therefore, we aimed to analyze treatment strategies and the prognosis of RLS caused by high-dose Madopar. Methods: Nine patients who were misdiagnosed with Parkinson’s disease, taking a high dose of Madopar, and showed symptoms of anxiety, depression, and somatization were recruited. Clinical data were collected, and strategies of treatment and prognosis were analyzed. Results: Seven patients demonstrated varying degrees of anxiety and depression, and the other two cases were misdiagnosed as Parkinson’s disease. During Madopar treatment, patients gradually showed aggravated symptoms, including swelling, numbness, pain, and other sensory abnormalities in both lower extremities, which spread to both upper extremities in a few patients. Among the seven patients, symptoms of anxiety, depression, insomnia, and somatization significantly worsened during the observation period. The average time from taking Madopar to the appearance of RLS was 2.6 ± 0.6 months, the average time to clinical diagnosis was 18.17 ± 9.40 months, and the average dosage of Madopar was 1.44 ± 0.21 g per day. Gradually reducing the Madopar dosage and administering a small dose of long-acting dopamine preparation greatly alleviated the symptoms after 3 months. Conclusion: A high dose of Madopar can cause RLS-like symptoms accompanied by anxiety, depression, insomnia, and other mental health symptoms. These symptoms should be more closely monitored by clinicians.